2020
DOI: 10.1101/2020.04.30.071217
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Permeability of the HIV-1 capsid to metabolites modulates viral DNA synthesis

Abstract: Reverse transcription, an essential event in the HIV-1 lifecycle, requires deoxynucleotide triphosphates (dNTPs) to fuel DNA synthesis, thus requiring penetration of dNTPs into the viral core.The central cavity of the capsid protein (CA) hexamer reveals itself as a plausible channel that allows the passage of dNTPs into assembled capsids. Nevertheless, the molecular mechanism of nucleotide import into the capsid remains unknown. Employing all-atom molecular dynamics simulations, we established that cooperative… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 55 publications
(62 reference statements)
1
9
0
Order By: Relevance
“…Together, these observations support a capsid stabilization mechanism for enhancement of ERT by IP6. In addition, studies involving computational modeling have suggested that IP6 binding to the HIV-1 capsid also facilitates the import of dNTPs into the viral core, an effect that may contribute to the enhancement of ERT observed in our experiments (34,35).…”
Section: Discussionmentioning
confidence: 63%
“…Together, these observations support a capsid stabilization mechanism for enhancement of ERT by IP6. In addition, studies involving computational modeling have suggested that IP6 binding to the HIV-1 capsid also facilitates the import of dNTPs into the viral core, an effect that may contribute to the enhancement of ERT observed in our experiments (34,35).…”
Section: Discussionmentioning
confidence: 63%
“…Subsequently, we observed that treatment of HIV-1 cores with IP6 appeared to accelerate the process, resulting in more rapid uncoating and possibly also reverse transcription (18). Under these conditions, the previously observed single stiffness peak was not apparent, perhaps owing to the low temporal resolution of the averaged stiffness measurements (~2 h) employed in that study, which may have obscured the more rapid aspects of the reactions.…”
Section: Analysis Of the Stiffness And Morphology Of Isolated Cores Umentioning
confidence: 71%
“…Recently, we used AFM to observe the physical changes in the HIV-1 core occurring during uncoating in vitro. We found that addition of capsid-stabilizing ligands, including the host protein cyclophilin A, the small molecule antiviral compound PF74, and the cell metabolite IP6, increased the stiffness of cores (18)(19)(20).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…IP6 also enhances mature capsid assembly and core stability leading to increased efficiency of encapsidated reverse transcription. Binding of IP6 to capsids is mediated by an electropositive pore that binds and facilitates the transport of deoxynucleotide triphosphates (dNTPs) into the capsid [ 51 , 52 ]. These data suggest a model in which IP6 facilitates assembly of the immature Gag lattice by stabilizing the six-helix bundle and is effectively packaged into virions.…”
Section: Introductionmentioning
confidence: 99%